The Effect of Service Quality, Price, and Promotion on Ojek Online Customer Loyalty (Case Study on Grab Customers in Tangerang City) - Elvin Kristin Gulo; Pujiarti Pujiarti (eCo-Buss, 2022)
The purpose of this study is to analyze and identify problems with online motorcycle taxis, especially regarding the effect of service quality, price and promotion on customer loyalty online motorcycle taxis (Grab) in the city of Tangerang. Data was collected through the distribution of questionnaires, where the questionnaires were distributed randomly to 100 respondents. Analysis of information used in this study is the acquisition of validity and reliability tests, classical assumption test, regression analysis, correlation analysis, coefficient of determination analysis, and hypothesis testing. The quality of service gets a tcount value of 2,935 where the value is 2,935 > 1.9872 with a significant value of 0.04 where the value is 0.04 < 0.05 so that H1 is accepted. The price gets a tcount value of 5.972 where the value is 5.972 > 1.9872 with a significant value of 0.00 where the value is 0.00 < 0.05 so H2 is accepted. The promotion gets a tcount of 4.300 where the value is 4.300 > 1.9872 with a significant value of 0.00 where the value is 0.00 < 0.05 so H3 is accepted. From the ANOVA test, Fcount is 80,163 where Fcount > Ftable with a value of 80,163 > 2.70, with a significant value of 0.00 where the value is 0.00 < 0.05 so it can be assumed that each independent variable (X) has a significant impact on the dependent variable (Y).